Thickness of Subcutaneous Fat Is a Predictive Factor of Incisional Surgical Site Infection in Crohn’s Disease Surgery: A Retrospective Study - Xingchen Cai; Weisong Shen; Zhen Guo; Yi Li; Lei Cao; Jianfeng Gong; Weiming Zhu (Gastroenterology Research and Practice)
Background. Incisional surgical site infection (iSSI) is a frequent postoperative complication of abdominal surgeries in patients with Crohn’s disease (CD). In this study, we investigated the association between thickness of subcutaneous fat (TSF) and iSSI in patients with CD undergoing intestinal resections. Patients and Methods. Patients with CD who had undergone abdominal surgery from January 2014 to January 2017 were included in this retrospective study. Patients’ TSF and other possible predictors of iSSI, including clinical characteristics, preoperative medications, hematological index, surgery-related data, and postoperative outcomes, were collected. Univariate and multivariate statistical analyses were used to examine the potential factors. Receiver operating characteristic (ROC) curve analysis was used to evaluate the predictive value of factors. Results. The patient cohort comprised 246 patients (167 male (67.9%); mean age 35.7 ± 12.4 years; mean disease duration 69.6 ± 60.8 months). The incidence of iSSI was 24.8% (61/246). TSF was a significant predictor of iSSI (OR 1.079, 95% CIs (1.020, 1.142), P=0.008), being 13.7 mm in patients with iSSI and 9.9 mm in those without iSSI (P<0.001). Additionally, C-reactive protein (CRP) concentrations (OR 1.059, P=0.003) were also possible predictors of iSSI, as indicated by both univariate and multivariate analysis. A model of iSSI comprising TSF and CRP concentrations was moderately accurate (AUC 0.827, CIs (0.766, 0.888)). Conclusions. Preoperative TSF and CRP independently affect iSSI in patients with CD undergoing intestinal resections.